The Effects of the Division of the City of Lloydminster by the Alberta-Saskatchewan Inter-Provincial Boundary - Dykstra, T.; Ironside, R. (Cahiers de géographie du Québec, 1972)
The paper traces the effects of the superimposed inter-provincial boundary line on the development of Lloydminster. Duplication of public services, and other difficulties encouraged early efforts to amalgamate the community under one jurisdiction. This was accomplished in 1930 and the city is operated under special legislation which is called the « Lloydminster Charter ». Inherent inefficiencies still remain for civic government as well as disadvantages for private enterprises as the provincial legislation of Alberta or Saskatchewan prevails depending upon which side of the boundary a person resides, works, shops, or an economic enterprise is located. The sales tax levied on most purchases by the Saskatchewan Government remains a problem for retailers and citizens. Most of the commercial and industrial development is occurring on the Alberta side of the City. There is evidence that industrial and commercial companies, professional people and residents, would prefer the City to be either in Alberta or Saskatchewan in order to eradicate the inefficiencies and irritations caused by the division of the city by the boundary.